Neoliberalism, economism and higher education - Samalavičius, Almantas (Cambridge Scholars Publishing, 2018)
This concise volume presents a series of conversations conducted by its editor with internationally renowned educators, scholars and social critics. The primary focus is on a set of important social and cultural issues and the complex nature of the global contemporary crises in higher education and economics, and the values and goals educational institutions pursue and produce. Contributors to this volume discuss why the present systems of higher education are ailing almost everywhere, and which remedies have turned out to be their poison. The contributions here investigate how and why universi.